Inheritance of extraordinary metabolic activity from parental bacteria individuals - Yuyang Lu; Jia Gao; Ruo-Chen Xie; Hua Su; Yaoyao Zhang; Wei Wang (Proceedings of the National Academy of Sciences, 2025)
Many phenotypic traits, such as fermentation activity, have been shown to be instable due to stochastic gene expression and environmental influence. While previous studies only have obtained understanding at the level of the microbial community, the fate of extraordinary traits of an individual through generations of reproduction has yet to be adequately investigated. This work uses the lactic acid bacteri Lactiplantibacillus plantarum as a research model to study the activity inheritance between parental generations and filial generations. An integrated single-cell manipulation strategy is established, including fluorescent screening using an extracellular pH probe and a microwell array, micropicking using a micropipette, and amplifying an individual bacterium via single-cell culture. Consequently, it is found that daughter bacteria can well inherit the strong acid-producing activity from their parental bacterial individuals, although as the reproduction proceeds over 30 generations, the offspring gradually regresses to the mediocre, thus setting a caveat for the limiting generations for desired inheritance. This is likely due to the deterioration of the cell living environment. This work illustrates the inheritable features of bacterial metabolic traits at the level of individual bacteria and is therefore fundamentally insightful for biotechnological applications like bioenergy production that require consistent or at least predictable metabolic performance.